Retorno Deportivo Luego de Reconstrucción Primaria de Ligamento Cruzado Anterior con Injerto Hueso-Tendón Patelar-Hueso Autólogo: Análisis de Factores Relacionados - Pakuts, A.; Martin, L.; Contador, J. (Revista Chilena de Ortopedia y Traumatología, 2020)
Objective Analyze return to sports and related factors after primary anterior cruciate ligament reconstruction.Methods Observational descriptive study. 173 patients operated by the same surgeon and standardized technique (patellar autograft) who answered a questionnaire at least 12 months post procedure were included. Questionnaire included Subjective IKDC, Tegner activity level (Pre and Postoperative) and questions elaborated by the group.Results Mean age was 30.8 years, 85% were men, 73% practiced soccer and median postoperative IKDC was 71. Follow up until questionnaire response was 28 months. Males had a better return to sports than females (70% vs 48%, p = 0.037). Tegner pre-injury level was 5 vs 4.3 postoperative, (p < 0.001). Return to sports was 67% according to Tegner scale and 66% by self-assessment. Return to similar previous activity level was 57% by Tegner scale but 24% by direct questions. Of those patients, 51% have fear of re-injury and 26% by reasons other than knee or surgery. We didn't find association between meniscal injuries and return to sports rate. Patients with chondral injuries had lower rates in return to sports (35% vs 60%, p = 0.002). Subjects that returned to sports had higher IKDC scores (73.5 vs 64.3, p < 0.001).Conclusions We found 67% return to sports and 57% to the preinjury level. Positive return to sports factors were male sex, absence of chondral injury and better functional outcome. Psychological factors such as fear of injury is frequent in patients who don't achieve previous levels of activity.
Keywords: anterior cruciate ligament; reconstruction; return to sports; kinesiophobia; bone patellar tendon bone